THE IMPLEMENTATION OF SHARIA BANKING ON THE ECONOMY OF SOCIETY IN INDONESIA - Andi Muhammad Reza (RADJA PUBLIKA, 2023)
The rapid development of Islamic banking in Indonesia, which must be balanced with contributions to economic growth, is the background for writing this article. The analysis in this article uses the Ordinary Least Square (OLS) method to find out how much influence Islamic banking has on economic growth as represented by the Gross Domestic Product. The financial sector plays an important role in driving a country's economic growth. This study aims to analyze the causal relationship between Islamic banking on Indonesia's economic growth, analyze the response of Indonesia's economic growth when shocks occur in Islamic banking variables, and determine the contribution of Islamic banking variables to Indonesia's economic growth. Total deposits, total credit/total financing, and total assets as a variable that represents banking. GDP (Gross Domestic Product) as a variable that represents economic growth. Using the Cointegration and Granger Causality methods, the results show that in general conventional and Islamic banking have an effect on economic growth in Indonesia.